2005
DOI: 10.1055/s-2005-868159
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Cerebral Revascularization for Patients with Atherosclerotic Carotid Occlusion

Abstract: Patients with complete carotid occlusion and recent ischemic symptoms are at high risk for subsequent stroke, particularly those with evidence of severe hemodynamic impairment due to poor collateral flow. Treatment options for these patients include direct extracranial to intracranial arterial bypass, or interventions aimed at improving collateral sources of flow such as endarterectomy or angioplasty and stenting of the ipsilateral external carotid artery, the contralateral carotid artery, or the vertebral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…2,30 In the 2003 publication on the European experience with revascularization in moyamoya disease, Khan et al 11 reported a significant reduction in transient ischemic attacks after 2 months in 20 of 23 patients with moyamoya disease who underwent STA-MCA bypass (with some undergoing additional indirect revascularizations).…”
Section: Superficial Temporal Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…2,30 In the 2003 publication on the European experience with revascularization in moyamoya disease, Khan et al 11 reported a significant reduction in transient ischemic attacks after 2 months in 20 of 23 patients with moyamoya disease who underwent STA-MCA bypass (with some undergoing additional indirect revascularizations).…”
Section: Superficial Temporal Arterymentioning
confidence: 99%
“…2,27 Achieving good clinical results depends not only on microsurgical technique but also on the selection of the appropriate graft. The 3 principal types of grafts historically used in cerebrovascular surgery include the saphenous vein, the RA, and the STA grafts.…”
mentioning
confidence: 99%
“…6 The presence of complete arterial occlusion does not reliably predict hemodynamic impairment in individual patients. 7,27 Certain patterns of collateral flow have been correlated with hemodynamic impairment, but the ability of these findings to identify individual patients with hemodynamic impairment has been poor. 8,37 Thus, in patients without characteristic limb shaking or orthostatic TIAs, which can be associated with hemodynamic impairment, 22 we relied on additional CT perfusion scanning data to determine the need for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Verschiedene Publikationen haben sich mit der Frage beschäftigt, wie häu-fig ein chronischer Karotisverschluss im weiteren Verlauf symptomatisch wird [21,22,23,24,25]. Dabei zeigte sich, dass ein asymptomatischer Karotisverschluss im weiteren Verlauf ein geringes Risiko von 3,3-4,7% hat symptomatisch zu werden, wohingegen beim symptomatischen Karotisverschluss ein Risiko von 18,5-26% besteht in den nächsten Jahren einen Reinfarkt auszubilden [21,22,23].…”
Section: Diskussionunclassified